Helicobacter pylori infection Evluated by C14-urea Breath test and it`s Relation with age, sex and ABO/Rhesus blood Groups in Patients with Gastrointestinal complaints in Kirkuk City / Iraq. - Nadia. M. Mohammad; Sabah M. Salih (Tikrit Journal of Pure Science)
There was significant difference between genders and H. pylori  infection (P<0.05). From the 176 patients attending private laboratories in Kirkuk city for the period from 1/8/2016 to 1/4/2017, 86(48.86%) belonged to blood group O, 42(23.86%) to A, 41(23.29%) to B and 7 (3.97%) to AB and There was statistically significant difference (P<0.05) in the incidence of H. pylori  infection between these groups, there was significant correlation between the presence of  particular blood group in H. pylori positive patients related to the reported frequency of the blood groups in Kirkuk population, the correlation between the Rh factor and positive H. pylori  patients was not significant to the frequency of the Rh factor in the population (88.06% Rh+ and 11.93% Rh-). the H. pylori  positive test was slightly, but not significantly lower in comparison with the negitive H. pylori patients test values showed a highly significant difference (P<0.01) in H. pylori posative and H. pylori negitive patients., in adults H. pylori  infection depend upon gender, blood groups but they do not depend upon the Patients age or Rh factore.